Electrophysiological and pharmacological investigation of caffeine-sensitive calcium release from intracellular calcium stores in cultured rat dorsal root ganglion neurones - Ayar, A. (My University, 2001)
The aim of this study was to investigate the actions of caffeine on intracellular calcium stores in cultured rat dorsal root ganglion (DRG) neurones using whole cell variant of the patch clamp and calcium imaging techniques. Extracellular caffeine (1mM) application activated inward currents in the presence and absence of extracellular Ca2+ but fail to activate any current when intracellular Ca2+ buffering capacity increased (using 20 mM EGTA), dantrolen or ryanodine was applied to the cells by the patch pipette solution. Calcium imaging studies using fura-2 confirmed the electrophysiological findings and provided further piece of evidence for caffeine-induced Ca2+ calcium release from ryanodine/dantrolene-sensitive intracellular Ca2+ stores. In conclusion caffeine releases Ca2+ from intracellular stores in DRG neurones and this effect of caffeine is sensitive to dantrolene.
Siçan dorsal kök gangliyon sinir hücre kültürlerinde hücre i?çi kalsiyum depolarindan kafeine duyarli kalsiyum saliverilmesinin elektrofizyolojik ve farmakolojik i?ncelenmesi
Keywords: Caffeine; Calcium; Cell culture; Patch-clamp; Sensory neurone